Prevalence, treatment, and control of severe hyperlipidemia - Matthew E. Gold; Michael G. Nanna; Shannon M. Doerfler; Tony Schibler; Daniel Wojdyla; Eric D. Peterson; Ann Marie Navar (Elsevier, 2020)
Objective: To identify the prevalence, treatment, and low-density lipoprotein cholesterol (LDL-C) control of individuals with LDL-C ≥190 ​mg/dL in contemporary clinical practice. Methods: We included adults (age ≥18 years) with LDL-C ≥190 ​mg/dL, at least one LDL-C level drawn from 255 health systems participating in Cerner HealthFacts database (2000-2017, n ​= ​4,623,851), and a detailed examination within Duke University Health System (DUHS, 2015-2017, n ​= ​267,710). Factors associated with LDL-C control were evaluated using multivariable logistic regression modeling. Results: The cross-sectional prevalence of LDL-C ≥190 ​mg/dL was 3.0% in Cerner (n ​= ​139,539/4,623,851) and 2.9% at DUHS (n ​= ​7728/267,710); among these, rates of repeat LDL-C measurement within 13 months were low: 27.9% (n ​= ​38,960) in Cerner, 54.5% (n ​= ​4211) at DUHS. Of patients with follow-up LDL-C levels, 23.6% in Cerner had a 50% of greater reduction in LDL-C, 18.3% achieved an LDL-C <100 ​mg/dL and 2.7% ​< ​70 ​mg/dL. At DUHS, 28.4% had a 50% or greater reduction in LDL-C, 28.4% achieved an LDL-C ≤100 ​mg/dL and 4.4% achieved <70 ​mg/dL. Within DUHS, 71.6% with LDL-C ≥190 ​mg/dL were on any statin during follow-up, but only 28.5% were on a high-intensity statin. In multivariable modeling, seeing a cardiologist (Cerner odds ratio [OR] 1.56, confidence interval [CI] 1.33-1.83; DUHS OR 1.89, 95% CI 1.18-3.01) and having diabetes (Cerner OR 1.34 CI 1.23-1.46; DUHS OR 2.07, CI 1.62-2.65) increased odds of LDL-C control, defined as a ≥50% reduction in LDL-C (at Cerner) or initiation of high intensity statin (at DUHS). Prior atherosclerotic cardiovascular disease (OR 1.19, CI 1.07-1.33), hypertension (OR 1.10, CI 1.03-1.18), African American race (OR 0.79, CI 0.71-0.89), and government (vs. private) insurance (OR 0.90, CI 0.83-0.98) were associated with LDL-C control at Cerner. Female sex was associated with lower odds of appropriate therapy (OR 0.69, CI 0.59-0.81) at DUHS. Conclusions: Approximately 3% of United States adults have LDL-C ≥190 ​mg/dL. Among those with very high LDL-C, rates of repeat measurement within one year were low; of those retested, only about one-fourth met guideline-recommended LDL-C treatment goals.